Analisis Gap pada Service Quality dengan Menggunakan Analytical Network Process pada Hotel JW Marriott Surabaya - Septian Sony Utomo; Indrianawati Usman; Ahmad Rizki Sridadi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This paper discusses the gap analysis of service quality dimensions with the Analytical Network Process (ANP) to explain how the management of the JW Marriott Surabaya Hotel in providing services to customers. The evaluation process is carried out by providing a questionnaire of customer perceptions and expectations with a Likert scale and then using ANP to determine the priority of evaluating service quality dimensions that can be used to find service quality gaps. The results show that 1) the largest gap occurs in the Price dimension, the second largest gap is the competency dimension, and the third largest gap is the responsiveness dimension, 2) the results of the evaluation priority level weighting indicate that the access and approachability dimensions have priority for improvement and evaluation, the second priority is the dimension of flexibility, and the third priority is the dimension of politeness. There are gaps in suitability, and gaps in market research, that have led some customers to leave negative reviews on the Booking.com site. Thus, it is necessary for the management of the JW Marriott Hotel to improve the quality of services provided so that hotel customers give a positive assessment and can even increase the number of customers of the JW Marriott Hotel Surabaya. In this case, even though the customer rating is good, the hotel management must always be willing and able to improve the quality of services provided because service quality is the most important thing in the hotel business.